Genderové souvislosti reforem důchodového systému v ČR - Radka Dudová (Gender a Výzkum)
The paper discusses changes that have occurred in the Czech pension system since 1996 in terms of their gender impact. The pension system is considered in a broader socio-economic context. I take into account different working careers of men and women and their unequal share in unpaid care work. I analyse individual steps of the reform (the criteria for entitlement to a retirement pension, changes in the mechanism for calculating pension benefits, and the newly established private second pillar) and show the impact of these changes on women and men in retirement. I conclude that although the reform is presented as gender-neutral just because it maintains the same conditions for both sexes, it ultimately brings significant deterioration in women’s retirement situation as compared to men’s. An increase in the level of equivalence—and therefore the increasing dependence of the pension entitlement on previous income from paid work—means that, in the logic of the pension system, unpaid work associated particularly with childcare is valued less and less and gender inequalities in the labour market are reproduced.